2020
DOI: 10.1021/acsmedchemlett.0c00045
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Pharmacological Evaluation of Second Generation EZH2 Inhibitors with Long Residence Time

Abstract: Histone methyltransferase EZH2, which is the catalytic subunit of the PRC2 complex, catalyzes the methylation of histone H3K27a transcriptionally repressive post-translational modification (PTM). EZH2 is commonly mutated in hematologic malignancies and frequently overexpressed in solid tumors, where its expression level often correlates with poor prognosis. First generation EZH2 inhibitors are beginning to show clinical benefit, and we believe that a second generation EZH2 inhibitor could further build upon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…A similar observation was made by incorporation of a 4-thiomethyl pyridone, recently reported to enhance EZH2 potency of compound 4 (Fig. 1) with increased residence time, 46 to provide compound 6e which exhibited biochemical and cellular potency similar to parent compound 2. Therefore, while the 4-SMe group was able to restore the potency lost due to N-methylation in compound 5, the desirable brain-penetrating properties gained through N-methylation were lost.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…A similar observation was made by incorporation of a 4-thiomethyl pyridone, recently reported to enhance EZH2 potency of compound 4 (Fig. 1) with increased residence time, 46 to provide compound 6e which exhibited biochemical and cellular potency similar to parent compound 2. Therefore, while the 4-SMe group was able to restore the potency lost due to N-methylation in compound 5, the desirable brain-penetrating properties gained through N-methylation were lost.…”
Section: Resultssupporting
confidence: 79%
“…This was surprising since this substitution has been associated with enhanced EZH2 potency through increasing residence time. 46 However, the SAR analysis for high affinity compounds is complicated by the enzymatic assay protein concentration of 5 nM resulting in a floor of the assay of 2.5 nM. For example, incorporation of the N-methyl pyridone into compound 20 displayed a greater than 500-fold loss of potency relative to compound 8 but the exact magnitude of the loss is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that, quite unexpectedly, the residence time of compound 2, the 4-thiomethyl analog of CPI-1205, ( Fig. 4 , A ), displayed an order of magnitude increase in inhibitor residence time ( 29 ) ( Fig. 4 , B ).…”
Section: Resultsmentioning
confidence: 86%
“…Further, in this work, we also expand the methodology for k on determination to enable fully quantitative potency assessments. Finally, we expand on the structure-kinetic relationships (SKRs) described previously (29) by showing the universality of the key structural motif to significantly enhance EZH2-inhibitor residence time across all scaffolds tested. The insights from our kinetic studies have enabled us to drive our second-generation series SAM-competitive EZH2 inhibitors to sub-pM biochemical potencies that correlate with enhanced tumor cell killing in vitro and in vivo.…”
mentioning
confidence: 79%
See 1 more Smart Citation